NEW MARKET PENETRATION STRATEGY: EXPANDING BEAUTY PRODUCTS TO GLOBAL MARKETS - Andri Riyadi; Luckhy Natalia Anastasye Lotte; Ryan Wajdy Hamas (Adisam Publisher, 2024)
The research aims to analyze new market penetration strategies in the expansion of beauty products to global markets. The method used is literary research involving a review of publications, articles, and books relevant to this topic. The findings of this study suggest that in order to successfully enter the global market, companies need to understand the needs and preferences of consumers in the target market, make product adjustments, formulations, and marketing strategies, invest in extensive distribution networks, and provide good customer support. The research also identifies some of the challenges that might emerge in expansion into global markets, such as cultural differences, regulations, and tighter competition.